Age as a predictor of COVID-19 severity in pediatric patients: a retrospective cohort study at a referral hospital in Peru - Chávez-Alvarado, Sara (2024)
Objective: To estimate the role of age as a predictor of COVID-19 severity in pediatric patients hospitalized with a COVID-19 diagnosis at a reference hospital in Peru. Materials and methods: A retrospective cohort study was conducted, including pediatric patients from one month old to less than 14 years of age, hospitalized between May 2020 and December 31, 2021, at the Edgardo Rebagliati-Martins National Hospital. The exposure variable was age, categorized in six-month intervals. The outcome variable was the severity of COVID-19, determined according to the severity criteria established in the EsSalud Clinical Practice Guidelines for the management of COVID-19 in pediatrics. Crude and adjusted relative risks (RR) were estimated, with their respective 95% confidence intervals (95% CI). Results: Three-hundred and thirty-one patients were analyzed, their median age was 94 months (7,8 years), and the male-to-female ratio was 1.23. Comorbidities were present in 59.5% of the patients, with neurological disorders being the most common (13.9%). Fatalities were 3.3% of the whole sample, and 63.6% of them were severe cases. Severe COVID-19 was found in 9.4% of the sample. In the adjusted regression model, increasing age was not found to be a predictor of reduced risk of COVID-19 severity (adjusted RR= 1.02; 95% CI 0.98-1.06). Conclusion: Our study did not find age as a predictor of COVID-19 severity in hospitalized pediatric patients. Future studies are recommended to further explore and contrast our findings.